Introducing EIS circuit elements in SPICE simulator environment - Kunaver, Matevž (Informacije MIDEM, 2025)
This study introduces hypothetical circuit elements, specifically the Constant Phase Element (CPE) and Zeroth-Order Approximation of a RC Circuit (ZARC), into the SPICE circuit simulation environment to enhance Electrochemical Impedance Spectroscopy (EIS) analysis. EIS, a critical method for understanding electrochemical processes in fields such as fuel cell analysis, corrosion studies, and biomaterials, relies on fitting measured impedance curves to Equivalent Electrical Circuit (EEC) models. However, existing approaches require expert knowledge and significant mathematical effort, limiting automation. By integrating CPE and ZARC into SPICE, this work bridges the gap between EIS analysis and advanced automatic circuit design methodologies, enabling efficient model selection and parameter determination. Experimental results demonstrate the accuracy of the implemented elements through a series of case studies, evaluated using Sheppard’s criteria function. This integration marks a significant step toward automated EIS model fitting and optimization, with potential implications for advancing electrochemical and materials research.
Keywords: circuit simulators; ekvivalentna električna vezja; electrochemical impedance spectroscopy; elektrokemična impedančna spektroskopija; equivalent electronic circuits; hipotetični elementi vezja; hypothetical circuit elements; simulatorji vezij